Analysis of Microstructure and Low Permeability with 3D Digital Rock Modeling. (3rd March 2022) - Wu, Jinsui; Xing, Min; Yin, Shangxian; Zhang, Ciyuan; Chen, Xuexi; Yi, Sihai; Lian, Huiqing; Xie, Dongyu
Abstract : The sandstone microstructure and permeability are important parameters for quantitative evaluation of groundwater/oil/gas resources and prediction of flow rates of water/oil/gas. In this study, we applied seven low-permeability sandstone samples obtained from North China to research the microstructure and permeability based on digital core technology. Rock images were collected by X-ray microcomputed tomography ( μ CT), and then software (Avizo) was applied to analyze the microstructure and calculate the parameters such as porosity, connected porosity, average equivalent diameter, tortuosity, and shape factor. By introducing the shape factor into the Kozeny–Carman equation, we modified the Kozeny–Carman equation and found that the modified equation is a function of porosity, diameter of particles, tortuosity, and particle shape factor.